PENGARUH PROMOSI DAN DIVERSIFIKASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI SUPERKUE CAKE AND BAKERY - Alsyabil, Delfia; Zaenal Muttaqin, Muhammad; Lukman Taufik, Akasahtia (An Nuqud Journal of Islamic Economics, 2025)
This research is motivated by the intense competition between entrepreneurs to increase sales of a product. Promotion is one of the strategies used in increasing product sales. The purpose of this study was to determine whether promotion and product diversification affect purchasing decisions at Superkue Cake and Bakery Leuwiliang. This research is a quantitative study that uses statistical analysis techniques such as validity tests, reliability tests, and chi-square tests. The results of the study of the chi-square test value of promotion with a purchase decision of 11.797 significance 0.001 <0.005. Furthermore, between diversification and purchasing decisions with the chi-square test results of 22.052 with a significance value of 0.000 <0.005. It can be concluded that promotion and product diversification carried out simultaneously have a major influence on consumer purchasing decisions